Crescimento e sobrevivência de juvenis de jundiás (Rhamdia quelen) em diferentes concentrações de ácido húmico, em pH ácido. - Costa, Sílvio Teixeira da (2012)
Humic acid is an organic substance identified in black waters, used as growth promoter and confers protection against environmental contamination by metals. The objective of this study was to evaluate survival and growth of juvenile silver catfish Rhamdia quelen exposed to different concentrations of humic acid at acidic pH, observing the morphological effects in the gills and erythrocytes. In the first experiment, juveniles were exposed to two pH (5.5 and 6.5) with concentrations (0, 10, 25 and 50 mg.L-1) of humic acid (CAT: H1 0.675-2 Aldrich® - humic acid sodium salt) for 40 days. In the second study the histological and morphometric parameters of gills of juveniles exposed to these treatments were analyzed. The third study evaluated the effect of different pH (3.8, 4.0, 4.2 and 7.0) and the concentrations of humic acid previously described on survival and erythroid morphology of juvenile silver catfish. Silver catfish showed greater weight, length, biomass, feed intake, and specific growth rate when exposed to pH 6.5 without the presence of humic acid. The gills of silver catfish exposed to pH 5.5 at 50 mg.L-1 of humic acid presented higher filament length, width of the lamellae, thickness of the epithelium of gill filament, lower distance between the lamellae, cell proliferation and increase in chloride gill respiratory surface area GRSA. There was also proliferation of chloride cells and increase in chloride cells fractional area (CCFA) of juveniles exposed to pH 5.5 at 50 mg L-1 humic acid. Survival of juveniles was impaired at pH 3.8 and pH 4.0, and the higher the concentration of humic acid, the lower the survival. Silver catfish exposed to pH 7.0 showed higher erythrocyte are than those exposed to pH 3.8, 4.0 or 4.2. The presence of humic acid caused an opposite effect, increasing red cells diameter in fish exposed to higher concentrations (50 mg.L-1). No changes in plasma Na+, K+, but at pH 3.8 the plasma levels of Cl- were lower than at neutral pH and this effect was potentiated by the increase of humic acid levels. Thus, it is concluded that the presence of synthetic humic acid in water is harmful to the developing juvenile catfish, the higher the concentration of humic acid in water, the higher is the water barrier and blood-cell proliferation chloride, changing the gill morphology of juvenile catfish, hematological parameters of juvenile silver catfish are also altered by the presence of synthetic humic acid, which could compromise adaptation and survival of this species in acidic pH, the humic acid protects against the juvenile catfish ionorregulatórios negative effects of exposure the acidic pH.